If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(x) = 2x + 1(x + 4) * 2x + 12 Multiply g * x gx = 2x + 1(x + 4) * 2x + 12 Reorder the terms: gx = 2x + 1(4 + x) * 2x + 12 Reorder the terms for easier multiplication: gx = 2x + 1 * 2x(4 + x) + 12 Multiply 1 * 2 gx = 2x + 2x(4 + x) + 12 gx = 2x + (4 * 2x + x * 2x) + 12 gx = 2x + (8x + 2x2) + 12 Reorder the terms: gx = 12 + 2x + 8x + 2x2 Combine like terms: 2x + 8x = 10x gx = 12 + 10x + 2x2 Solving gx = 12 + 10x + 2x2 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by 'x'. g = 12x-1 + 10 + 2x Simplifying g = 12x-1 + 10 + 2x Reorder the terms: g = 10 + 12x-1 + 2x
| (3xy+1)(2xy-3)= | | 12-4x=-15+2x | | x^6=1296 | | 5y-8x=8x | | f(x)=x+4(2x+1)8x^2+4 | | 4-6(2x-3)+1=3+7(5-x) | | 2-8m=14-3+8m | | t^2-24=2t | | k^2-20k-35=0 | | g(x)=x+7(2x)2x+14 | | 11/18x^2-7x-56=0 | | 0.6111x^2-7x-56=0 | | 4(x+2)=3(2x-(6-x)) | | 35x+12=4x+3 | | f(x)=2x(x+7)2x^2+14 | | 30=(5/9)(F-32) | | 30(9/5) | | x=(3)(3)(3) | | (6x+7)(2x+1)= | | 5n^2+13n-28=0 | | -4.9t^2+10t+2=0 | | 8-9p=1 | | 15a^2-22a-5=0 | | (3a+2)(a-2)= | | (-3)-(-10)= | | ((-7)-3)((-3)-(10))= | | x/5-x/10=3 | | 2x^4-6x^3+x^2+3=0 | | 13(2-x)=7(x+8) | | 5x+3x^2=25 | | c/a-p/a=1 | | f(x)=tan*3*x |